SVM-GA Based A Novel Technique for the Detection of the Vehicle in an Optimized Overlapped Multi-Camera System - Madhukaro, Joshi Rakhi; Rao, D. S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The presence of CCTV cameras on highways helps enhance public safety and instills a sense of security among road users. It promotes responsible behavior, discourages reckless driving, and can aid in resolving disputes related to accidents or incidents. This research proposes an innovative and very trustworthy approach to identify vehicles on the road. This paper also examines vehicle tracking in the presence of uncalibrated Cameras with overlapping fields of view used to capture images, which are characteristics of traffic surveillance systems. To discover a greater accuracy of the desired field of vision in such a situation, it is crucial to create and construct a system to compute the road geometry and establish correspondence between the positions of the multiple cameras. We outline a special technique for automatically identifying traffic camera angle positions using a collection of dimensions and the GA-SVM machine learning algorithm followed by the novel vehicle detection architecture.